Campylobacter enteritis in children in Enugu, Nigeria - Ngozi F Onyemelukwe; Bede C Ibe (International Journal of Medicine and Health Development, 1998)
Campylobacter jejuni was isolated from the stools of 47 out of 636 children (7.4%) aged 5 years, with acute diarrhoea. Significantly more children from the rural than from the urban environment had C. jejuni enteritis (26/224 Vs 21/407, P 0.01). There were no differences with respect to sex. The age group at greatest risk were the 7-12 months old. Campylobacter jejuni is an important aetiological agent of bacterial diarrhoea in children and should be routinely looked for while investigating childhood diarrhoea especially if the child is under two years of age.